PENGARUH ADAPTASI KEWIRAUSAHAAN DAN KARAKTER WIRAUSAHA TERHADAP KINERJA USAHA PENGOLAHAN MAKANAN DI KABUPATEN BUNGO - Yudhi Novriansyah; Ainun Ainun (POLITEKNIK LP3I JAKARTA, 2022)
This study is entitled The Effect of Entrepreneurial Adaptation and Entrepreneurial Character on Food Processing Business Skill in Bungo Regency. The object of this research is Small Business Actors in the field of Food Processing in Bungo Regency Participants of Food Operator Training Batch 1-IV in 2021. This study uses a purposive sampling technique with a sample of 67 people. The data processing used multiple regression analysis and SPSS software version 25. The results of the study found that Entrepreneurial Adaptation had an effect on Food Processing Business Performance in line with Vera Dwi Cahyani's research (2017), while Entrepreneurial Character had an effect on Food Processing Business Skill in line with the research of Nurul Fikri (2018).Keywords: Entrepreneurial Adaptation, Entrepreneurial Character, Food Processing